U1 Asymptomatic lymphogranuloma venereum in known hiv positive msm: is it more common than we think?. (18th May 2015) - Ward, Daniel; Boothby, Meg; Goold, Penny; Hathorn, Emma
Abstract : Background/introduction: The primary manifestation of lymphogranuloma venereum (LGV) infection in men who have sex with men (MSM) in the United Kingdom (UK) is haemorrhagic proctitis with very low levels of asymptomatic infection reported. Aim(s)/objectives: To evaluate LGV infection in MSM attending a large inner city sexual health and human immunodeficiency virus (HIV) clinic. Methods: Data was retrospectively collected on all MSM diagnosed with rectal Chlamydia trachomatis (CT) from 1 st October 2010 to 30 th June 2014. Information was collected on presentation, LGV diagnosis, HIV status, concurrent sexual infection, treatment and sexual contacts. Results: 583 MSM had a new diagnosis of rectal CT during the study period of which 173 (29.7%) were known to be HIV positive. 118 MSM (20.2%; 64 HIV negative; 54 HIV positive) underwent additional testing for LGV and 32 infections (26 HIV positive MSM) were confirmed. All asymptomatic LGV infections (n = 5; 15.6%) were diagnosed in HIV positive MSM whilst all HIV negative MSM with LGV infection were symptomatic. Discussion/conclusion: We report a higher incidence of asymptomatic LGV infection in MSM than previously reported. Whilst the number of confirmed LGV infections is low, results suggest screening for LGV infection may be appropriate in all HIV positive MSM with confirmed rectal CT regardless of symptomatology.